Health beliefs, attitude, psychological factors and self management practices of out-patients with chronic non-insulin dependent diabetes in the Northern Province of South Africa - Bopape, Mantwa Welhemina (University of Limpopo, 2000)
Refer to document
Thesis (M.A. (Psychology)) -- University of Limpopo, 2000
Keywords: Health beliefs; Psychological factors; Self management practices; Out-patients; Cronic non-insulin dependents diabetes; South Africa; Non-insulin-dependent diabetes; Attitude (Psychology); Self-management (Psychology); Patient self-monitoring; Chronic diseases; Diabetes -- Psychological aspects